2011
DOI: 10.3727/096368910x564094
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Conditions during Expansion Culture Prime Human Mesenchymal Stromal Precursor Cells for Chondrogenic Differentiation in Three-Dimensional Cultures

Abstract: Cell-based approaches using mesenchymal stromal precursor cells (MSCs) for the regeneration of intervertebral discs are attracting increased interest, even though the intervertebral disc is a very demanding environment. Implanted cells eventually face acidic pH, hypoxia, and a lack of nutrients. While the regenerative potential of MSCs for skeletal tissues has been well described, it is still questionable whether human MSCs can be prepared for prolonged survival and proper functioning and whether they can diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 54 publications
5
46
0
Order By: Relevance
“…High oxygen concentration promotes osteogenic differentiation and induces bone formation and mineralization [156,157]. Low oxygen concentration favors chondrogenic differentiation, upregulates collagen type II and type X expression, and downregulates collagen I expression [150,158,159]. Thus, tight coordination of oxygen concentration and spatial and temporal presentation of angiogenic and/or antiangiogenic factors will be essential to generate a tendon/ligament-to-bone construct with appropriate vascularization.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…High oxygen concentration promotes osteogenic differentiation and induces bone formation and mineralization [156,157]. Low oxygen concentration favors chondrogenic differentiation, upregulates collagen type II and type X expression, and downregulates collagen I expression [150,158,159]. Thus, tight coordination of oxygen concentration and spatial and temporal presentation of angiogenic and/or antiangiogenic factors will be essential to generate a tendon/ligament-to-bone construct with appropriate vascularization.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…There was no effect of growth in serum-free medium when it was compared to our standard growth medium which contains 2% serum, growth factors and cytokines [14]. We hypothesized that reduced oxygen concentration during culture would increase WJC expansion rates and CFE since previous work had shown that reduced oxygen concentration during culture has potent effects on expansion of bone marrow-derived MSCs [29][30][31][32][33][34][35] and WJCs [36,37]. We speculated that plating density would impact WJC expansion based upon previous work using bone marrow-derived MSCs which had shown that MSC have more rapid expansion after plating a low density [38].…”
Section: Discussionmentioning
confidence: 99%
“…Research by O'Connor [44] has shown that NSCs can proliferate and differentiate in 3D collagen gels; Ma [12] has vaccined NSCs in collagen matrix for proliferation and Successful 3D cell bioprocessing depends on the supply of nutrients and cytokines [45]. At the same time, a stable physiological environment is also necessary, i.e., temperature, pH, and oxygen [45][46][47]. The concentration of nutrients and metabolites should be strictly monitored and controlled during cultivation since it affects cell growth, viability, and differentiation.…”
Section: Discussionmentioning
confidence: 98%